Juridical Analysis of PTUN Decision No. 128/G/PTUN-MDN Regarding the Dismission of Civil Servants Without Respect from the Perspective of Fiqih Siyasah - Bayu Rizky Wirawan; Muhammad Ramadhan (Journal Equity of Law and Governance, 2024)
This study aims to conduct an in-depth analysis of PTUN Decision No. 128/G/PTUN-MDN concerning the dismissal of civil servants (PNS) without honor. Utilizing a fiqh siyasah approach, this research explores the juridical and administrative aspects of the decision. In the legal context, the study examines the compliance of the decision with various applicable regulations, including Law No. 5 of 2014 on State Civil Apparatus, which regulates the procedures and processes for dismissing civil servants. Additionally, this research assesses whether the dismissal process has been carried out in accordance with the principles of good governance, such as transparency, accountability, and participation. From the perspective of fiqh siyasah, this study aims to evaluate the legitimacy of government actions in dismissing civil servants and their impact on justice and the protection of individual rights. The analysis includes a comparison with Islamic principles related to justice and human rights. The findings indicate that the PTUN decision serves not only as a means of legal enforcement but also reflects the ethical and moral values that should be upheld in governance. This decision can be seen as a manifestation of efforts to create justice in public administration and the necessity of considering moral aspects in every government action. This research contributes significantly to the understanding of the complex relationship between law, public administration, and Islamic values in public policy, emphasizing the importance of integrating fiqh siyasah principles into governmental decision-making.